Authorship and Peer Review: Practices and Perception of Spanish Early Career Researchers - Rodríguez-Bravo, Blanca; Nicholas, David (Revista General de Información y Documentación, 2020)
The study analyzes the pinions and practices of the Spanish Early Career Researchers (ECRs) regarding co-authorship and peer review obtained from a survey’s data. It is observed that ECRs contribute to all the tasks of an investigation, although their merit is not always sufficiently recognized. They would like the signing order to be regulated and reflect the work of each author. They also actively participate in the peer review process, both in the role of authors and of reviewers. They ask for improvements in reviewing but they seem moderately satisfied with a process that, although hard, is enriching. Between the possibilities they are conservative, prefer to be protected by anonymity and consequently support the double-blind model.